2008
DOI: 10.1189/jlb.0907631
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cyclic-AMP response element binding protein contributes to adiponectin-stimulated interleukin-10 expression in raw 264.7 macrophages

Abstract: Adiponectin, an adipokine predominantly secreted from adipose tissue, has potent anti-inflammatory properties. Although the mechanisms for the anti-inflammatory properties of adiponectin are not well understood, recent evidence suggests that increased production of interleukin-10 (IL-10), a potent immunomodulatory cytokine, is involved in the anti-inflammatory actions of adiponectin. Globular adiponectin (gAcrp) increased IL-10 promoter activity and IL-10 mRNA accumulation in RAW 264.7 macrophages. Deletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 46 publications
2
34
0
1
Order By: Relevance
“…On the other hand, adiponectin treatment significantly elevated the IL10 level within the colon and plasma. This observation is in agreement with in vitro studies whereby adiponectin induced macrophage IL10 expression [43]. In contrast to our findings and Nishihara's group, a recent study showed that adiponectin KO mice are protected from DSS and TNBS colitis, and adiponectin treatment induces inflammation [44].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, adiponectin treatment significantly elevated the IL10 level within the colon and plasma. This observation is in agreement with in vitro studies whereby adiponectin induced macrophage IL10 expression [43]. In contrast to our findings and Nishihara's group, a recent study showed that adiponectin KO mice are protected from DSS and TNBS colitis, and adiponectin treatment induces inflammation [44].…”
Section: Discussionsupporting
confidence: 88%
“…IL10 mediated p38 mitogen-activated protein kinase (p38MAPK) signaling can block activation of the ER stress sensor-endoplasmic reticulum-binding protein (BIP)-after exposing intestinal cells to TNFa [63]. Adiponectin can induce IL10 and activate p38MAPK [64,65]. We now show that adiponectin treatment decreased ER stress response.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that acute exercise activates MAPK p38 which could stimulate IL-10 gene expression and protein synthesis (Ikeda et al 2007;Park et al 2008). Also, IL-6, a potent inducer of anti-inXammatory cytokines such as IL-10 and inhibitor of TNF-production (Pedersen 2007;Mathur and Pedersen 2008), may have contributed to the increase in the IL-10/TNF-ratio of muscles in the exercised groups .…”
Section: Discussionmentioning
confidence: 96%
“…Because most studies have been conducted using LPS as a stimulus, the control of IL-10 expression by Stat3 has been considered a general paradigm so far (9 -12). Further evidence that distinct stimuli might use distinct transcription factors has recently been reported by showing that during the ingestion of apoptotic cells by murine macrophages, the synthesis of IL-10 is under the control of Pbx1b (20) and by the involvement of CREB in the regulation of IL-10 production by murine macrophages stimulated with adiponectin (47).…”
Section: Discussionmentioning
confidence: 96%